Restorative benefits of multisensory experiences in a classical Chinese garden compared to visual experiences only - Cai, Yanning; Sun, Minkai; Lu, Yudie; Wang, Yuqin; Goto, Seiko (Frontiers in Psychology, 2025)
BackgroundClassical Chinese gardens are renowned for their multisensory designs and are widely recognized for their potential to promote emotional well-being. The Humble Administrator’s Garden was utilized in this study to assess how the multisensory integration embedded in its design influences psychological and physiological restoration.MethodsAs a pilot study, a multi-modal quantitative approach compared participants’ responses to the garden under two conditions: a real-world multisensory environment (Condition A) and a visual VR experience using a static 360° image (Condition B). The same group of 28 participants took part in five-minute sessions for each condition. Data included the Profile of Mood States (POMS), heart rate, eye tracking, and a questionnaire. In Condition A, sessions before 8:00 a.m. with few visitors were classified as the “Uncrowded group,” while those after 8:00 a.m., when tour groups arrived, were classified as the “Crowded group,” to assess visitor-related ambient effects on restoration.ResultsParticipants in the real-world condition exhibited significantly greater mood modulation, increased attentional engagement, and a reduction in heart rate, particularly in uncrowded settings. In contrast, the VR condition yielded comparatively weaker restorative outcomes, suggesting that both the absence of non-visual inputs and the lack of visual movement limited the replication of the multisensory restorative experience.DiscussionThis pilot study suggests that the restorative effects of classical Chinese gardens derive from the coherence of multisensory inputs, more fully experienced in real settings through visual and non-visual interactions. While multisensory coherence supports psychological benefits, disturbances such as noise and crowding can disrupt this harmony, weakening restorative outcomes. These exploratory findings offer initial guidance for the development of restorative virtual environments and the management of heritage sites, while underscoring the need for larger-scale and more immersive studies.